Achieving Sustainable Development Goals in Bangladesh: Does Population Density Matter? (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Bangladesh, one of the most densely populated countries in the world with a density of about 1,265 persons per km2 having a limited land area with high development potential. Being able to accomplish noteworthy achievements in MDGs, Bangladesh is heading towards achieving the targets of the SDGs amid several challenges like high population, resource constraints, poverty etc. This study aims at addressing the challenges and prospect of increasing population density in achieving the SDGs. An exploratory approach has been applied to address how the density of population might influence the achievement of the SDGs. Data on population and other relevant parameters have been identified from census, published documents and articles. The current progress of SDGs attainment shows some of the goals are on track, but more progress could have been achieved unless being hindered by the high density of population. Feeding and providing the basic amenities to this huge population is quite a big challenge with limited resources, in contrast, optimum utilization of the demographic dividend by ensuring effective participation of the young active population in the current development process can also expedite the progress of attainment of SDGs. The adversities of the high density of population can essentially be offset by redistribution of urban population and decentralization of economic activities from major cities. Alongside appropriate and precise policy measures, comprehensive study on quantifying how the density of population is affecting the attainment of SDGs is recommended.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(2), 2019, P 1-15